Effect of olive mill wastewater phenolic extract, whey protein isolate and xanthan gum on the behaviour of olive O/W emulsions using response surface methodology. (December 2016) - Caporaso, Nicola; Genovese, Alessandro; Burke, Róisín; Barry-Ryan, Catherine; Sacchi, Raffaele
Abstract: Spray-dried polyphenols extracted from olive mill wastewater (OMW) were used to formulate 20% olive oil-in-water (O/W) emulsions stabilised with whey protein isolate (WPI) and xanthan gum at pH 7. The effects of olive biophenol extract (0.9–4.4 mM), whey protein isolate (0.13–0.5%) and xanthan gum (0.06–0.2%) on the physical stability (creaming index), viscosity, emulsion droplet size and distribution, primary and secondary oxidation products were assessed over accelerated storage of emulsions. Response surface methodology (RSM) was applied for experimental design using three-factor central composite design (CCD) with 3 central points. The effects of OMW phenolics, WPI and xanthan gum were statistically significant on emulsion creaming rate, viscosity, PV, TBARS and cloudiness. Second-order polynomial models were obtained for predicting these responses, resulting in good performances especially for the first two responses. High coefficient of determination ( R 2 ) values ranging from 0.847 to 0.973 were obtained for creaming and viscosity, acceptable R 2 values were obtained for lipid oxidation parameters (peroxide value and TBARS) and cloudiness value, while non-significant results were obtained for mean droplet size. The performance of the model was particularly good for creaming rate and viscosity. It has been highlighted that the interactions between OMW phenolic extract and the ingredients studied should be considered for the formulation of olive O/W emulsions. This research could be useful for the formulation of functional food products based on O/W emulsions, as well as understanding the physico-chemical interactions among olive biophenols, whey proteins and xanthan gum. Graphical abstract: Highlights: Olive O/W emulsions were produced with polyphenols, whey proteins and xanthan gum. Powder phenolic extracts were obtained from olive mill wastewater. Emulsion behaviour was successfully described using central composite design for RSM. Xanthan gum has dramatic effects on physical stability but more limited on oxidation. Protein-polyphenols interactions had statistically significant effects on the model.